PERAN GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Fatolosa Hulu (Jurnal Education and Development, 2021)
The purpose of this study was to identify and describe the teacher's role in increasing student interest in learning. The approach used in this research is a qualitative approach and the type of descriptive research. The data sources in this study were Pancasila and Citizenship Education teachers, amounting to 1 person as a respondent and 5 students as informants. Data collection techniques were carried out through the stages of (1) observation, (2) interviews, (3) documentation studies. Data analysis was carried out through three activity lines (1) data reduction, (2) data modeling, (3) conclusion drawing/verification. Based on the findings in the field, that the competence of teachers has been carried out well as professional educators with the main task of educating, teaching, guiding, directing, training, assessing and evaluating students in the formal education path.